Efficacy and safety of catheter ablation for atrial fibrillation in congenital heart disease – A systematic review and meta-analysis - Pranata, Raymond (Indian Pacing Electrophysiol J, 2019)
BACKGROUND: Prevalence of atrial fibrillation (AF) in patients with congenital heart disease (CHD) is on the rise. Anti-arrhythmic drugs are usually the first line of treatment in CHD, however, it is often ineffective and poorly tolerated. We aimed to perform a systematic review to assess the efficacy and safety of catheter ablation for AF in CHD. METHODS: We performed a comprehensive search on catheter ablation for atrial fibrillation in congenital heart disease up until July 2019 through several electronic databases. RESULTS: Ablation of AF in patients with CHD had a modest 12 months AF freedom ranging from 32.8% to 63%, which can be increased by subsequent/repeat ablation. The complexity of CHD appears to have a significant effect on a study but not in others. Catheter ablation in ASD and persistent left superior vena cava had a high success rate. Overall, catheter ablation is safe whichever the type of CHD is. CONCLUSION: Catheter ablation for AF in CHD had modest efficacy that can be increased by subsequent/repeat ablation and it also has an excellent safety profile. Ablation in complex CHD could also have similar efficacy, however, it is preferably done by experts in a high volume tertiary center.